2020
DOI: 10.1021/acsomega.9b03472
|View full text |Cite
|
Sign up to set email alerts
|

Effective Stabilization of Perovskite Cesium Lead Bromide Nanocrystals through Facile Surface Modification by Perfluorocarbon Acid

Abstract: CsPbX3 (X = Cl, Br, I) perovskite nanocrystals (NCs) have attracted much attention as promising materials for next-generation optoelectronic applications. However, improvement of their low stabilities against heating and humidity is needed for practical use. In this work, we focused on perfluorodecanoic acid (PFDA) as a surface ligand and investigated the thermal and chemical stabilities of the photoluminescence (PL) properties of CsPbBr3 NCs. Oleic acid (OA) adsorbed on the NCs was exchanged for decanoic acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 58 publications
1
28
0
Order By: Relevance
“…[ 291 ] Fluorinated perfluorodecanoic acid has been used to replace native oleate and tetraoctylammonium ligands, resulting in an enhanced PL intensity (increased in PL QY from 72% to 90%), and a better stability against ethanol. [ 292 ] Bidentate 2,2′‐iminodibenzoic acid replaced oleic acid through ligand exchange, resulting in a significant increase in PL QY, stability, and NC shelf life. [ 293 ] Improvement of these properties was attributed to the two binding sites of the 2,2′‐iminodibenzoic acid ligand, leading to enhanced NC passivation.…”
Section: Postsynthetic Ligand Modifications In Lhp Ncsmentioning
confidence: 99%
“…[ 291 ] Fluorinated perfluorodecanoic acid has been used to replace native oleate and tetraoctylammonium ligands, resulting in an enhanced PL intensity (increased in PL QY from 72% to 90%), and a better stability against ethanol. [ 292 ] Bidentate 2,2′‐iminodibenzoic acid replaced oleic acid through ligand exchange, resulting in a significant increase in PL QY, stability, and NC shelf life. [ 293 ] Improvement of these properties was attributed to the two binding sites of the 2,2′‐iminodibenzoic acid ligand, leading to enhanced NC passivation.…”
Section: Postsynthetic Ligand Modifications In Lhp Ncsmentioning
confidence: 99%
“…For example, protecting the surface of the NCs with various materials, such as silica, aluminosilicate, or polymer resin, has been shown to improve their photostability. Strong coordination of surface ligands can also enhance the stability of NCs; therefore, surface engineering is an important approach to consider for enhancing the photostability of CsPbX 3 NCs.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 7 presents the electrical output characteristics of the device fabricated with NCs. [75] Sato et al showed that the PL intensity of perfluorodecanoic acid (PFDA)-modified CsPbX 3 (X=Cl, Br, and I) was retained by 92.1% even after heating at 100°C for 4 hours, whereas the OA-modified CsPbX 3 NCs exhibited fluorescence quenching to 12.9% of initial PL intensity. Along with PL property, resistance against polar solvents was significantly improved by these modified NCs which could find their place in practical applications.…”
Section: Cspbbr 3 Nanocrystalsmentioning
confidence: 99%
“…This improved efficiency is ascribed to the better film morphology and low defect states of OPA‐capped perovskite NCs. Figure 7 presents the electrical output characteristics of the device fabricated with NCs [75] . Sato et al.…”
Section: Surface Passivation Strategiesmentioning
confidence: 99%